Mobile Tourism Research and Practices: A Comprehensive Bibliometric Exploration and Future Study Direction - Syaifullah Syaifullah; Shamsul Arrieya Ariffin; Norhisham Mohamad Nordin (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
Even though mobile tourism analysis is developing, there is still a lack of literature regarding its formation patterns which makes the picture of its evolution incomplete. The evaluation in this study was carried out in general by emphasizing the evolution of exploratory analysis on the theme of